Unusual Case of Retropancreatic Mass Involving Portal Vein - Poudel, Rajesh; Adhikari, Subodh K; Basnet, Surendra; Acharya, Arjun; Pokhrel, Sarad (Journal of Universal College of Medical Sciences, 2018)
Retroperitoneal Tumors are relatively rare and usually present in locally advanced stage. They present special therapeutic challenges because of their location and frequent intimate association with major vessels in retroperitoneum. Herein, we present a case report of a patient with retropancreatic mass along with features of portal hypertension in CT scan. Intraoperatively tumor was adhered to portal vein, resection and anastomosis of Portal Vein with excision of tumor was done. Leiomysarcoma was diagnosed after histopathology and immunohistochemistry report.Journal of Universal College of Medical Sciences, Vol. 5, No. 2, 2017, Page: 49-52